Problematizing the Diversity Debit Hypothesis - Alexei Anisin (Journal of BRICS Studies)
One of the most studied hypotheses in political economy and development literature posits that social heterogeneity is negatively associated with favorable societal and political outcomes. This study problematizes the diversity debit hypothesis. It overviews its theoretical underpinning and uncovers its roots to be in rational choice theory and the homo economicus framework of human behavior. As such, scholarly accounts of diversity debit have attributed it to the agency (or lack thereof) of minority groups and their impaired ability to engage in collective mobilization to pressure elites for concessions. Through case studies of three most-different countries: the US, Turkey, and Vietnam, this study discovers that even when mass mobilization has been waged by minority groups either along ethnic or cross-ethnic boundaries, it has not led to favorable outcomes. Diversity debit has subsisted and will likely continue to exist not as a result of individual failure, but due to the interaction of structural (neoliberal capitalistic) forces with the agency of either government-led actions (antagonization and discrimination of minority groups) and corporate profiteering.